Pengaruh Kompetensi Dan Budaya Kerja Terhadap Kinerja Sales Marketing Pada Pt. Danamas Insan Kreatif Andalan Dan PT. Bank Central Asia Kantor Cabang Lampung - Saputra, Yoga; Budiarti, Riskha Tri; Alfarezi, Muhammad (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
This study examines the effect of competence and work culture on sales marketing performance at PT Danamas Insan Creative Andalan and PT Bank Central Asia Lampung Branch. This research uses quantitative research methods with a descriptive approach with data analyzed using SPSS v17.0. The results show that competence and work culture have a significant effect on sales marketing performance. Competence, as measured by the understanding of organizational values and its application to the organization's personality, has a significant effect with a tcount> ttable value (3.55> 1.67). This means that the hypothesis that competence affects performance is accepted. Work culture, as measured by the quality of the elements that build it, also has a significant effect on performance with a tcount value > ttable (3.57 > 1.67). This means that the hypothesis that work culture affects performance is accepted. This research proves that competence and work culture both play an important role in improving sales marketing performance at PT Danamas Insan Creative Andalan and PT Bank Central Asia Lampung Branch.